Fabrication of hierarchical CoP/ZnCdS/Co3O4 quantum dots (800>40>4.5 nm) bi-heterostructure cages for efficient photocatalytic hydrogen evolution - Li, Yanbing; Zhu, Pengfei; Tsubaki, Noritatsu; Jin, Zhiliang (Renewable energy, 2022)
The design and construction of hierarchical CoP/ZnCdS/Co₃O₄ quantum dots (QDs) (800 > 40>4.5 nm) bi-heterostructure cages as an ultrahigh-performance photocatalyst for hydrogen evolution with visible light is investigated. Three excellent photoactive materials that ZnCdS solid solution, high-conductivity CoP and high-efficiency Co₃O₄ QDs were integrated into all-in-one bi-heterostructure cages architecture. The development of the two high-efficiency electron-transfer pathways in CoP/ZnCdS/Co₃O₄ QDs can seriously facilitate the separation and migration of light-induced electrons while the unique structure also can offer large reaction surface and expose abundant active sites for photocatalytic hydrogen evolution reaction. Because of the distinctively compositional and structural merits, the hierarchical CoP/ZnCdS/Co₃O₄ QDs bi-heterostructure cages without introducing any cocatalysts exhibit ultrahigh activity and favorable stability for generation of high-purity hydrogen under visible light irradiation. In comparison with pure ZnCdS nanoparticles (8.2 mmol‧g⁻¹‧h⁻¹) and 1.5 wt.% CoP/ZnCdS (12.4 mmol‧g⁻¹‧h⁻¹), the new-structure CoP/ZnCdS/Co₃O₄ QDs (O/ZCS/P-3) exhibits more excellent hydrogen evolution performance (24.2 mmol‧g⁻¹‧h⁻¹) under 5 W LED light irradiation, and the hydrogen evolution rate is up to 40 mmol‧g⁻¹‧h⁻¹ under 300 W xenon lamp irradiation.